Study on the shear-pretension coupling behavior of 3D uniform and variable thickness woven fabrics. (March 2023) - Li, Mengran; Zhang, Binbin; Liu, Kai; Liu, Zengfei; Qiao, Jianwei; Huang, Jian; Liang, Jun
Abstract: Pretension is regarded as an effective way to suppress the draping defects caused by the excessive shearing deformation of preforms during the manufacturing of woven composites. However, the research of shear-pretension coupling behavior on the 3D woven fabric uniform and variable thickness structures has not been carried out. In present study, the behavior of the two kinds of woven fabric structures is investigated. The picture frame shear test for fabrics are conducted with applied pre-tension for the work. The relationship between shear stress and shear angle under different pre-tension levels of the two kinds of fabrics is analyzed. Furthermore, the detailed comparison of shear-pretension coupling behavior between the two kinds of woven fabric structures is also analyzed. Finally, the effect of variable thickness condition on the in-plane shear properties for woven fabric variable thickness structure is investigated. The research provides experimental data support for the forming design of preforms of heterogeneous 3D composite structures. Highlights: The shear-pretension coupling behaviors of uniform and variable thickness 3D woven fabrics are investigated. The pre-tension force enhances the ability of 3D woven fabrics to resist shear deformation. Providing data support for the design of 3D woven preforms for heterogeneous composite structures.